Prevalence and Risk Factors of Problematic Internet Use among Undergraduate Medical Students of Bangladesh (IAHS Medical Journal, 2022)
Background: Problematic Internet Use (PIU) is now a global social issue and comprises an important area of research since its negative consequences have been found as a stumbling block to our everyday functioning, interpersonal relationships and emotional well-being. Several severe psychiatric symptoms, depressive episodes, attention deficit hyperactivity disorder (ADHD) and alcohol abuse, are pronounced in those who regard themselves as dependent on the internet. To estimate the prevalence and risk factors of problematic internet use among undergradute medical students of Bangladesh, this study was done.Materials and methods: This study was a descriptive cross-sectional type of study conducted among randomly selected 280 undergraduate medical students in selected medical colleges in Bangladesh from July to December 2021. All the data were computed and analyzed with the proper statistical method.Results: 62.9% of the participants had some form of Problematic Internet Use (PIU). The prevalence of severe PIU was found to be 3.6%. 32.1% of the subjects were normal users, and 25.7% had moderate PIU. Mild PIU was noted among 38.6% of the participants. Medical students who spend more than 3 hours daily on the internet (p